2022
DOI: 10.1088/1741-4326/ac5fea
|View full text |Cite
|
Sign up to set email alerts
|

Sideways forces on asymmetric tokamak walls during plasma disruptions

Abstract: In the quarter century since the danger of sideways force on tokamak wall during disruptions was first recognized, substantial progress has been made in understanding the connection between plasma kink and the force. Less is known, however, about the effect of the wall asymmetry on the force generation. Here, we explore how irregularly situated ports lead to large sideways forces even for a symmetric driver such as a typical current quench. Further, we compare the effectiveness of both mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…To test this idea a dedicated modelling effort with the CarMa0NL code [57] that solves the evolutionary equilibrium of axisymmetric plasma in the presence of three-dimensional volumetric conductors has been performed [58]. It was found that the sideways force related to the vessel non-uniformity can be as high as 3 kN (for the mesh shown in figure 13(c)), which is 17% of the maximum vertical force for the same disruption.…”
Section: Sideways Forces On the Wall During Plasma Disruptionsmentioning
confidence: 99%
“…To test this idea a dedicated modelling effort with the CarMa0NL code [57] that solves the evolutionary equilibrium of axisymmetric plasma in the presence of three-dimensional volumetric conductors has been performed [58]. It was found that the sideways force related to the vessel non-uniformity can be as high as 3 kN (for the mesh shown in figure 13(c)), which is 17% of the maximum vertical force for the same disruption.…”
Section: Sideways Forces On the Wall During Plasma Disruptionsmentioning
confidence: 99%
“…In tokamaks, the wall force due to disruptions may lead to a global horizontal displacement of the whole torus as reported in JET experiment [1]. Such wall force is called sideways force and it is related to asymmetric magnetic perturbations due to the symmetry-breaking plasma deformations [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] or wall non-uniformity along the toroidal direction (asymmetric wall) [21,22]. In a Cartesian system of coordinates-where the z axis corresponds to the torus axis-sideways force corresponds to F x and F y components of the integral wall force while the remaining F z component is the vertical force.…”
Section: Introductionmentioning
confidence: 97%